Employee coaching and counseling program metode alternatif untuk optimalisasi human capital pada pegawai aparatur sipil negara (ASN) - Marina Sulastiana; Rezki Ashriyana Sulistiobudi; Azhar El Hami (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2017)
: State Civil Servants Apparatus (ASN) have to be more integrity, professional, neutral and capable to carrying out a public service to the community. It was an important one that can be optimized through development of human capital. Based on previous research investigated role of Human Capital towards Services and performance of Public Service, shows that staff and head divison level only has moderate degree of human capital. While, Emotional Capital was a most dominan aspect in Human Capital. Otherwise, Social Capital aspects results in the low level. It comes with consequences to optimized them through psychological intervention with group Employee Coaching and Counseling Program (ECCP). This study was action research, experimental one group preteset and postest design. The result shows that ECCP was contribute effectively to enhance Human Capital, particularly in Emotional Capital optimization.